Salvador López Quero y José Mª Maestre Maestre (eds.), Studia Angelo Urbano Dicata, Alcañiz-Madrid, Instituto de Estudios Humanísticos-Federación Andaluza de Estudios Clásicos, 2015, 458 pp. ISBN 978-84-96053-80-9 | 978-84-96053-81-6 (Minerva, 2019)
Review:  Salvador López Quero y José Mª Maestre Maestre (eds.), Studia Angelo Urbano Dicata, Alcañiz-Madrid, Instituto de Estudios Humanísticos-Federación Andaluza de Estudios Clásicos, 2015, 458 pp. ISBN 978-84-96053-80-9 | 978-84-96053-81-6